Survival and causes of mortality of introduced wild pigs in the presence of cougars - Mitchell A. Parsons; Kurt C. Vercauteren; Justin A. Dellinger; Julie K. Young (Biological Invasions, 2025)

A Functional Response in Resource Selection Links Multiscale Responses of a Large Carnivore to Human Mortality Risk - Kyle D. Dougherty; Justin A. Dellinger; Bogdan Cristescu; Daniel J. Gammons; David K. Garcelon; J. Mark Higley; Quinton E. Martins; Seth P. D. Riley; Jeff A. Sikich; Thomas R. Stephenson; T. Winston Vickers; Greta M. Wengert; et al. (Ecology Letters, 2025)
Theory suggests that animals make hierarchical, multiscale resource selection decisions to address the hierarchy of factors limiting their fitness. Ecologists have developed tools to link population‐level resource selection across scales; yet, theoretical expectations about the relationship between coarse‐ and fine‐scale selection decisions at the individual level remain elusive despite their importance to fitness. With GPS‐telemetry data collected across California, USA, we evaluated resource selection of mountain lions ( Puma concolor ; n = 244) relative to spatial variation in human‐caused mortality risk. With hierarchical resource selection, coarse‐scale selection determines availability at finer scales. This simple relationship allowed us to demonstrate that functional responses in resource selection explicitly link individual‐level resource selection decisions across scales. We show that individuals proactively avoiding risk when selecting home ranges are freed to relax this avoidance when making decisions within home ranges. However, individuals also exhibit reactive avoidance of risk at the finest scales along movement paths.

Development of a 95 SNP panel to individually genotype mountain lions (Puma concolor) for microfluidic and other genotyping platforms - Michael R. Buchalski; Benjamin N. Sacks; Kristen D. Ahrens; Kyle D. Gustafson; Jaime L. Rudd; Holly B. Ernest; Justin A. Dellinger (Conservation Genetics Resources, 2022)
The mountain lion ( Puma concolor ) is one of the few remaining large predators in California, USA with density estimation from fecal genotypes becoming an essential component of conservation and management. In highly urbanized southern California, mountain lions are fragmented into small, inbred populations making proper marker selection critical for individual identification. We developed a panel of single nucleotide polymorphism (SNP) markers that can be used for consistent, routine mountain lion monitoring by different laboratories. We used a subset of existing Illumina HiSeq data for 104 individuals from throughout California to design a single, highly heterozygous multiplex of 95 SNPs for the Fluidigm platform. This panel confidently differentiates individual mountain lions, identifies sex, and discriminates mountain lions from bobcats. The panel performed well on fecal DNA extracts and based on design, had sufficient resolution to differentiate individual genotypes in even the population with lowest genetic diversity in southern California.

Kill rates and associated ecological factors for an apex predator - Bogdan Cristescu; L. Mark Elbroch; Justin A. Dellinger; Wesley Binder; Christopher C. Wilmers; Heiko U. Wittmer (Mammalian Biology, 2022)
Kill rates and functional responses are fundamental to the study of predator ecology and the understanding of predatory-prey dynamics. As the most widely distributed apex predator in the western hemisphere, pumas ( Puma concolor ) have been well studied, yet a synthesis of their kill rates is currently lacking. We reviewed the literature and compiled data on sex- and age-specific kill rate estimates of pumas on ungulates, and conducted analyses aimed at understanding ecological factors explaining the observed spatial variation. Kill rate studies on pumas, while numerous, were primarily conducted in Temperate Conifer Forests (< 10% of puma range), revealing a dearth of knowledge across much of their range, especially from tropical and subtropical habitats. Across studies, kill rates in ungulates/week were highest for adult females with kitten(s) (1.24 ± 0.41 ungulates/week) but did not vary significantly between adult males (0.84 ± 0.18) and solitary adult females (0.99 ± 0.26). Kill rates in kg/day differed only marginally among reproductive classes. Kill rates of adult pumas increased with ungulate density, particularly for males. Ungulate species richness had a weak negative association with adult male kill rates. Neither scavenger richness, puma density, the proportion of non-ungulate prey in the diet, nor regional human population density had a significant effect on ungulate kill rates, but additional studies and standardization would provide further insights. Our results had a strong temperate-ecosystem bias highlighting the need for further research across the diverse biomes pumas occupy to fully interpret kill rates for the species. Data from more populations would also allow for multivariate analyses providing deeper inference into the ecological and behavioural factors driving kill rates and functional responses of pumas, and apex predators in general.

Habitat use of sympatric prey suggests divergent anti-predator responses to recolonizing gray wolves - Justin A. Dellinger; Carolyn R. Shores; Apryle Craig; Michael R. Heithaus; William J. Ripple; Aaron J. Wirsing (Oecologia, 2019)

The ecological effects of providing resource subsidies to predators - Thomas M. Newsome; Justin A. Dellinger; Chris R. Pavey; William J. Ripple; Carolyn R. Shores; Aaron J. Wirsing; Christopher R. Dickman (Global Ecology and Biogeography, 2015)
Aim Predators often have important roles in structuring ecosystems via their effects on each other and on prey populations. However, these effects may be altered in the presence of anthropogenic food resources, fuelling debate about whether the availability of such resources could alter the ecological role of predators. Here, we review the extent to which human‐provided foods are utilised by terrestrial mammalian predators (> 1 kg) across the globe. We also assess whether these resources have a direct impact on the ecology and behaviour of predators and an indirect impact on other co‐occurring species. Location Global. Methods Data were derived from searches of the published literature. To summarise the data we grouped studies based on the direct and indirect effects of resource subsidies on predators and co‐occurring species. We then compared the types of predators accessing these resources by grouping species taxonomically and into the following categories: (1) domesticated species, (2) mesopredators and (3) top predators. Results Human‐provided foods were reported to be utilised by 36 terrestrial predator species in 34 different countries. In the presence of these resources we found that: (1) predator abundance increased, (2) the dietary preferences of predators altered to include the food subsidy, (3) life‐history parameters such as survival, reproduction and sociality shifted to the benefit or detriment of the predator, and (4) predators changed their home ranges, activity and movements. In some instances, these modifications indirectly affected co‐occurring species via increased predation or competition. Main conclusions The availability of human‐provided food to predators often results in behavioural or population‐induced changes to predators and trophic cascades. We conclude that there is an urgent need to reduce the access of predators to food subsidies to minimise human–wildlife conflicts and to preserve the integrity of ecosystem functioning in human‐influenced landscapes world‐wide.